The influence of digit ratio and achievement motivation on endurance performance in handball talents - Tirp, J.; Büsch, D.; Strauß, B.; Baker, J.; Pabst, J.; Kungl, A. M.; Schorer, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The influence of nature and nurture on sporting peak performance has been widely discussed (Baker & Davids, 2007). A potential biomarker that seems to influences sporting performance, es-pecially in endurance activities, is the ratio between the second and the fourth digit (2D:4D digit ratio)(Hönekopp & Schuster, 2010). Interestingly, endurance is also a highly trainable capability, requiring sustained motivation over an extensive period. The aim of this study was to investigate whether endurance performance in handball talents is determined more by digit ratio or achieve-ment motivation. Methods: 220 boys (M age = 15.1 years) and 176 girls (M age = 14.1 years) from a national talent selection camp were examined for this study. Endurance performance was measured using a shuttle run test and digit ratio was determined using digital photographs. Athletes` also completed the Achievement Motivation Scale (AMS). Results: For boys there was a significant correlation between shuttle run test and digit ratio, r = -.14, p = .04. The correlation between shuttle run test and AMS also reached significance, r = -.20, p < .01, but the association between digit ratio and AMS was not significant, r = -.01, p =.89. For girls the correlation between shuttle run test and AMS just failed significance, r = -.15, p = .06. The correla-tions between shuttle run test and digit ratio, r = -.07, p = .39, and digit ratio and AMS, r = -.12, p = .12 were non-significant. Conclusion: Our results suggest endurance performance is not strongly associated with digit ratio or achieve-ment motivation in handball talents. While our results indicated significance in males the explained variance was below five percent. Hönekopp and Schuster (2010) showed strong correlations be-tween endurance performance and digit ratio and it is possible our results may be best explained with the homogeneity of the group (cf. Lidor et al., 2005). A deeper insight might be gained from investigating this question in more heterogeneous groups